The Influence of Balcony Railing Form Quality Visual Fasade of Flat House - Erwin Djuni; Dyan Agustin; Niniek Anggriani (Nusantara Science and Technology Proceedings)
In the flats the government provides a balcony or a back porch on each dwelling that serves to relax with the family to enjoy the outside view as well as a place for entry of fresh air from outside. From the results of the questionnaire it was found that the most frequent activities of residents on the balcony were drying clothes (38%), then cooking (28%) and bathing (24%). While the smallest are eating (5%) and sitting sitting (5%). This is due to the unavailability of a place for drying clothes so that most residents use balconies for drying clothes. The condition of flats, especially balconies, has decreased in quality and occurs in the technical, functional, and aesthetic aspects of the building, as seen from the condition of the balconies that have experienced a lot of changes in shape and function. From the observations it was found that the decrease in balcony quality was due to the shape of the railing. This study uses a rationalistic approach with a qualitative deductive method conducted on balcony railings in several flats. The purpose of this study is to find answers about the effect of balcony railing shape on the visual quality of the Flats facade. From this research, the results show that balcony railings with vertical arrangement have a worse influence on the visual quality of the apartment facade compared to the horizontal arrangement. This is because the horizontal arrangement of residents cannot put their clothesline out of the balcony (on the outside). Thus, the visual quality of the apartment vasade will remain awake and avoid the impression of slums due to the hanging clothesline.